2020
DOI: 10.1021/acs.est.0c01559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quantitative Polymerase Chain Reaction Data Analysis Using Sample Amplification Efficiency on Microbial Source Tracking Assay Performance and Source Attribution

Abstract: The widely used microbial source tracking (MST) technique, quantitative polymerase chain reaction (qPCR), quantifies host-specific gene abundance in polluted water to identify and prioritize contamination sources. This study characterized the effects of a qPCR data analysis using the sample PCR efficiencies (the LinRegPCR model) on gene abundance and compared them with the standard curve-based method (the mixed model). Five qPCR assays were evaluated: the universal GenBac3, human-specific HF183/BFDrev and CPQ_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
2
6
1
Order By: Relevance
“…The MST marker abundance was investigated in surface water near the mixed land use of industrial and residential areas. Fecal contamination was indicated by GenBac3 level in this study (four to eight orders of magnitude in log 10 copies/100 ml), which were slightly lower than those found in untreated sewage in Thailand (five to nine orders in log 10 copies/100 ml) (Kongprajug et al, 2020), but slightly higher than the Tha Chin River in Central Thailand (three to seven orders in log 10 copies/100 ml) (Kongprajug et al, 2019a). These GenBac3 levels were aligned with levels found in other geographical regions in urban rivers (five to seven orders), urban recreational beaches (two to five orders), and karst springs (four to seven orders) (Molina et al, 2014;Ohad et al, 2015;Devane et al, 2019).…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…The MST marker abundance was investigated in surface water near the mixed land use of industrial and residential areas. Fecal contamination was indicated by GenBac3 level in this study (four to eight orders of magnitude in log 10 copies/100 ml), which were slightly lower than those found in untreated sewage in Thailand (five to nine orders in log 10 copies/100 ml) (Kongprajug et al, 2020), but slightly higher than the Tha Chin River in Central Thailand (three to seven orders in log 10 copies/100 ml) (Kongprajug et al, 2019a). These GenBac3 levels were aligned with levels found in other geographical regions in urban rivers (five to seven orders), urban recreational beaches (two to five orders), and karst springs (four to seven orders) (Molina et al, 2014;Ohad et al, 2015;Devane et al, 2019).…”
Section: Discussioncontrasting
confidence: 65%
“…A general fecal marker, GenBac3 (Siefring et al, 2008), two human-specific fecal markers, human polyomavirus BK and JC (HPyVs) (McQuaig et al, 2009) and crAssphage (Stachler et al, 2017), and adenovirus types 40/41 (HAdV40/41) (Ko et al, 2005) were used in this study (Supplementary Table 2). The abovementioned MST markers were selected because they have been investigated and validated in Thailand (Kongprajug et al, 2019a(Kongprajug et al, , 2020Sangkaew et al, 2021), and HAdV40/41 was chosen because it has been identified as the second most prevalent following the subgroup C from child patients with acute gastroenteritis in Thailand (Kumthip et al, 2019). A 20-µl qPCR reaction contained 0.8 µl of each 10 µM forward and reverse primers, 0.4 µl of 10 µM probe, 2 µl of extracted DNA, 6 µl of 1 µg/µl BSA, and 10 µl of the 2X iTaq Universal Probes Supermix (Bio-Rad, United States).…”
Section: Quantitative Pcr (Qpcr) Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…However, heterogeneity in published standard curves for SARS-CoV-2 has been observed (Bivins, Kaya, et al, 2021). Moreover, variations in technical and laboratory analyses (e.g., data analysis methods and control materials) could intensify biases, leading to variability in the calculated virus concentrations (Bivins, Kaya, et al, 2021; Kongprajug, Chyerochana, et al, 2020). Adhering to standards and quality control measures is therefore underlined in order to support data sharing and referencing for future research, especially for emerging infectious diseases.…”
Section: Resultsmentioning
confidence: 99%